Choice of Rotation Rate for the Horizontal Clinostat - Lyon, Charles J. (1970)
A series of nine rates of rotation of the clinostat were tested to determine optimal and acceptable conditions for simulating weightlessness in plants. Young seedlings of wheat (Triticum aestivum L.) developed roots and coleoptiles of equal lengths and with the same orientation angles over a range of rotation rates from 0.25 to 480 minutes per revolution. Rates from 0.25 to 3 minutes per revolution provided for maximal epinastic curvatures of leaves and branches of Coleus blumei Benth. except for a reduced mean curvature of branches at 0.25 minute per revolution, due probably to physical disturbances in their growth. Smaller epinastic curvatures developed in both leaves and branches rotated at 15 minutes per revolution or more slowly. Indoleacetic acid-2-(14)C was used for measurements of extractable radioactivity in determining the reason for smaller curvatures of Coleus branches and tomato (Lycopersicon esculentum Mill.) leaves at the rotation rate of 60 minutes per revolution than at 1 minute per revolution. The cause was determined to be movement of some auxin from the upper into the lower side of a plagiotropic leaf or branch under the transient influence of gravity during rotation on the slower clinostat. A rotation period of 1 to 3 minutes was found to be acceptable for most plants.